David Cameron et la campagne du « Remain » - Pauline Schnapper (Revue Française de Civilisation Britannique)
This article analyses the reasons why the Remain campaign, led by David Cameron, failed to convince a majority of the British voters to stay in the European Union on the 23 June 2016. It first analyses the structural reasons underestimated by the Prime Minister, in particular the general eurosceptic climate in his country, strengthened by the multiple crises confronted by the EU since 2008. It then analyses the political factors which constrained the Remain campaign and finally the tactical mistakes made during the campaign, in particular the failure to articulate a clear message on immigration, which left the floor open to the Leave campaign.